Whales of the Inuvialuit Settlement Region in Canada's Western Arctic: An Overview and Outlook - Harwood, Lois A.; Smith, Thomas G. (ARCTIC, 2002)
The beluga whale (Delphinapterus leucas) and the bowhead whale (Balaena mysticetus) are seasonal migrants to Canada's Western Arctic, occupying summer range in the southeastern Beaufort Sea and Amundsen Gulf within the Inuvialuit Settlement Region (ISR). These whales also travel through United States (Alaskan) and Russian offshore waters, which include migration routes and overwintering areas for both species. The beluga has for centuries been an important food resource of the aboriginal people of the Mackenzie Delta. From 1990 to 1999, the annual subsistence harvest of beluga in the ISR averaged 111, while only two bowheads were landed during this same period. The minimum size of the Eastern Beaufort Sea beluga stock has been estimated at 32 453 whales. The total annual removal of beluga by subsistence hunters from the ISR and Alaska is estimated at 189 whales, which is less than 0.6% of the minimum estimate of stock size. This level of harvest is sustainable. Between 1848 and 1921, commercial whalers decimated the Bering Sea population of bowhead whales. The size of the population, based on 1993 data, is estimated at 8200 (95% estimation interval of 7200-9400), constituting more than 90% of the world's remaining bowheads. This population increased at a rate of 3.2% from 1978 to 1993, while sustaining a harvest of about 0.6% per year. To ensure the continued well-being of these whales and their habitats, it is recommended that existing monitoring programs, commitments, and co-management partnerships be nurtured and maintained. Le béluga (Delphinapterus leucas) et la baleine boréale (Balaena mysticetus) sont des migrateurs saisonniers qui fréquentent l'ouest de l'Arctique canadien, occupant un territoire estival dans le sud-est de la mer de Beaufort et le golfe Amundsen au sein de la Région désignée des Inuvialuit (RDI). Ces baleines se déplacent également dans les eaux situées au large des États-Unis (alaskiennes) et de la Russie, qui comprennent des voies migratoires et des aires d'hivernage pour les deux ...